Bi‐/multilingual creativity in Indian English. Issue 3 (8th October 2018) - Gargesh, Ravinder
Abstract: The article highlights the contribution of Larry E. Smith in the contexts of English as an International Language and world Englishes. It views Larry's framework of intelligibility, comprehensibility and interpretability that led to an egalitarian view about the different varieties of Englishes.